PROBLEMS FOR FORMATION OF CIVIL IDENTITY AS A SOCIO-POLITICAL PHENOMENON OF CIVIL SOCIETY - Когiakovtseva Olga; Bugaychuk, Tatyana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The article presents the material revealing the problems of the formation of civil identity and civic position in children and youth and determining the features of the socio-political development of the individual in the conditions of the educational organization and the family in the period of social transformations. The authors of the article emphasize the development of "activity of the spirit," that is, the basic value orientations, which should precede the development of "activity of action", therefore attention to civic-patriotic education in the conditions of educational organizations and family should be a priority.